2024
DOI: 10.13057/biodiv/d241239
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry suitability evaluation using remote sensing in Jatiyoso Sub-district, Karanganyar District, Central Java, Indonesia

SNADA INDAH TUK NEGARI,
SESILIA RETNO AYU NINGTYAS,
ZAHRA HANUN
et al.

Abstract: Abstract. Negari SIT, Ningtyas SRA, Hanun Z, Sulton MN, Kusumaningrum L, Indrawan M, Sugiyarto, Sutomo, Setyawan AD. 2023. Agroforestry suitability evaluation using remote sensing in Jatiyoso Sub-district, Karanganyar District, Central Java, Indonesia. Biodiversitas 24: 6761-6769. Agroforestry systems are critical for biodiversity conservation, land degradation mitigation, and climate change mitigation. This agroforestry approach reduces forest degradation, boosts food security, and gradually raises farmers' i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…We found that elevation makes the most contribution (25.1%) to the suitable habitat of the species. Elevation is one of the variables driving plant development (Negari et al 2023). The P. merkusii may survive in both warm and cold climates within elevation range between 200 and 2000 m asl (Siregar and Diputra 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We found that elevation makes the most contribution (25.1%) to the suitable habitat of the species. Elevation is one of the variables driving plant development (Negari et al 2023). The P. merkusii may survive in both warm and cold climates within elevation range between 200 and 2000 m asl (Siregar and Diputra 2013).…”
Section: Discussionmentioning
confidence: 99%